Diagnosis Penyakit THT Menggunakan Metode Fuzzy K-NN - Afrida Djulya Ika Pratiwi; Dian Eka Ratnawati; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Humans are one of the living beings that exist in the world. One of the important organs that exist in humans are the ears, nose, and throat. This causes the organs to be connected to each other and can cause the spread of infection if one of the three organs are infected. Diseases that attack ENT is still considered trivial by the community, so the public awareness to check to the doctor is still low. Therefore, to facilitate the community to making their own diagnosis of ENT disease, then made a diagnosis system ENT disease. This diagnostic system uses Fuzzy-K nearest neighbor method. The used of the Fuzzy-K nearest neighbor method occurs in some studies that using this method can get high scores. In this study using four pieces of testing, namely testing of variations in the amount of training data, testing of variations in the number of values ​​k., testing of comparison between the number data training and data testing, and cross validation testing. Based on four types of test scenarios performed using 122 data related to ENT disease, obtained results with an average rate of 99,2%.